Perceived Risk of Cigarette Smoking Among College Students - Aryal, R R; Lohani, S P (Journal of Nepal Health Research Council, 2011)
Background: Many studies have indicated that the young adults (18-24 years) were not fully aware of healthconsequences of cigarette smoking. The objective of the study is to determine the prevalence of cigarette smoking among college students and to assess how they perceive the risks of cigarette smoking. Methods: A cross-sectional study was carried out in Kathmandu valley during mid February and March 2011. This study comprises 340 students from seven private public health colleges of Kathmandu valley. The anonymous question contains information on demographic characteristics, smoking habits, and smoking related risk perception. Data was analyzed by both descriptive and inferential statistics including logistic regression with the help of Microsoft Excel 2007 and SPSS 11.5 version. Results: Overall prevalence rate of ever smokers was 33% and about 16% were current smokers. Non-smokers were about 3 times more likely than smokers to report that smoking one to five cigarettes per day was harmful (aOR =2.60; 95% CI: 1.34-5.05). Similarly, Non Smokers were 2 times more likely to belief the statement that people get addicted to tobacco as to cocaine or heroin (aOR =2.27; 95%CI: 1.33-4.57). Nearly one fifth of smokers and non-smokers believed that smoking on a weekend or a couple of days a week was harmful, and there was no significant difference between two groups (P>0.05). Conclusions: The study reveals the smoker students were less aware of risks of cigarette smoking and its health consequences. Thus there is a need to promote effective anti-smoking messages focusing effects of each cigarette they smoke. Keywords: college students, smoking, risk perceptions.